2021
DOI: 10.12962/j25481479.v6i3.9451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Diesel Engine Components Durability on Fishing Vessel Fueled with Biodiesel (B30)

Abstract: ⎯ the Indonesian government's policy of using biodiesel as an alternative fuel in the shipping industry is still an intensive discussion. Biodiesel as a substitute for diesel fuel has an impact on engine performance, lifetime and emission. The use of biodiesel fuel will increase the wear rate on metal components in diesel engines. From a series of tests carried out in accordance with Engine Manufacturer Association (EMA) standards, wearing on several engine components would be increase when the engine run usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Where: P = Power (W) mf = Fuel Consumption (kg/jam) LHV = Low Heating Value (kj/kg), for diesel oil = 43400 kj/kg [22] ηth = (0.0695625/(0.09897 x 43400) x 3600) x 100 = ((0.88 x 0.1) / 309) x 3600 = 5.83%…”
Section: A Diesel Engine Performance Testing Processmentioning
confidence: 99%
“…Where: P = Power (W) mf = Fuel Consumption (kg/jam) LHV = Low Heating Value (kj/kg), for diesel oil = 43400 kj/kg [22] ηth = (0.0695625/(0.09897 x 43400) x 3600) x 100 = ((0.88 x 0.1) / 309) x 3600 = 5.83%…”
Section: A Diesel Engine Performance Testing Processmentioning
confidence: 99%
“…Chromium content was also found in the same sample. It also found cases of loosened piston rings and journal bearings experiencing wear [15]. The International Maritime Organization (IMO), an agency under the auspices of the United Nations, has set a target of reducing world carbon emissions by 40% in 2030 and 70% in 2050 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the use of Biodiesel (B30) showed that there was an aluminum metal content of 19.8%, an iron content of 0.75%, and a chromium content in diesel engine lubricating oil, in addition, to an increase in piston ring clearance and wear on the journal was also found. bearings [10].…”
Section: Introductionmentioning
confidence: 99%